2013
DOI: 10.1111/jnc.12482
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiological consequences of acute footshock stress: effects on tyrosine hydroxylase phosphorylation and activation in the rat brain and adrenal medulla

Abstract: Stress activates selected neuronal systems in the brain and this leads to activation of a range of effector systems. Our aim was to investigate some of the relationships between these systems under basal conditions and over a 40-min period in response to footshock stress. Specifically, we investigated catecholaminergic neurons in the locus coeruleus (LC), ventral tegmental area and medial prefrontal cortex (mPFC) in the brain, by measuring tyrosine hydroxylase (TH) protein, TH phosphorylation and TH activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 56 publications
(75 reference statements)
2
72
0
Order By: Relevance
“…There are several reports on elevation of both TH and TPH2 following exposure to various other types of stressors. [80][81][82][83][84] Supporting our observations, Tümer and colleagues 85 also have reported significant increases in TH protein levels in the adrenal medulla (20%) and an even higher increase in nucleus tractus solitarii of the brain stem (49%), and showed that this increase is associated with elevated plasma norepinephrine levels (23%) 6 h post-exposure to blast. The authors have linked this upregulation of the sympathetic system to elevated oxidative stress in the hypothalamus.…”
Section: Tbi and Monoamine Synthesizing Enzymessupporting
confidence: 84%
“…There are several reports on elevation of both TH and TPH2 following exposure to various other types of stressors. [80][81][82][83][84] Supporting our observations, Tümer and colleagues 85 also have reported significant increases in TH protein levels in the adrenal medulla (20%) and an even higher increase in nucleus tractus solitarii of the brain stem (49%), and showed that this increase is associated with elevated plasma norepinephrine levels (23%) 6 h post-exposure to blast. The authors have linked this upregulation of the sympathetic system to elevated oxidative stress in the hypothalamus.…”
Section: Tbi and Monoamine Synthesizing Enzymessupporting
confidence: 84%
“…Here, we find that recombinant CNTF induces significant Ser 31 phosphorylation of TH, along with prototypic Erk1 phosphorylation (Haycock et al , 1992) in cranial pons explants containing the LC (45 and 58% increase in the phosphorylated forms of TH and Erk, respectively, *P  <   0.05; Fig 3D–D2; Appendix Fig S2B). When applying subcutaneous formalin stress, Ser 31 phosphorylation of TH was transient (~twofold at 20 min, P  <   0.05) and eluded its Ser 40 residue, which seems unrelated to augmenting NE synthesis upon pain‐induced stress (Ong et al , 2014; Appendix Fig S2C and C1). To substantiate that ventricular ependyma is the source of CNTF to induce TH activity in LC, we performed site‐directed Cntf silencing through icv siRNA infusion (Fig 3E).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, achieving 100% compliance in this regimen does not require the employment of electric footshock. Indeed, elimination of electric footshock is imperative in order to interpret the impact of exercise on behavioral measures that depend upon catecholamines, especially dopamine, given the long-known impact of stressors like footshook upon catecholamine biosynthesis 17–18 .…”
Section: Discussionmentioning
confidence: 99%
“…This is a critical point for consideration, particularly for those investigators involved in behavioral studies that are influenced by dopamine- or norepinephrine-signaling. Electrical footshock is a physiological stressor, and its impact on both neurotransmitter systems is well-documented, with increased activation of tyrosine hydroxylase 17–18 . Thus, increased biosynthesis of either neurotransmitter could confound the interpretation of any exercise effect, making the investigator liable for interpreting whether any observed change in behavior after exercise is strictly due to the exercise regimen or the footshock stress.…”
Section: Introductionmentioning
confidence: 99%